Simultaneous UV Spectrophotometric Determination of Cetrizine and Dextromethorphan in Tablet Dosage Form - R. Vijayalakshmi; S. Bhargavi; M. D. Dhanaraju (E-Journal of Chemistry)
Two accurate, precise, sensitve and economical procedures for simultaneous estimation of cetrizine and dextromethorphan in tablet dosage forms have been developed. First method employs formation and solving of simultaneous equations using 230 nm and 280 nm as two analytical wavelengths for both drugs in methanol. The second method is Q-analysis based on measurement of absorptivity at 224 nm (as isobestic point) and 280 nm (λmax of CTZ). Cetrizine and dextromethorphan at their respective λmax 280 nm and 230 nm and at 224 nm (isobestic point) shows linearity in a concentration range of 10-30 mcg/mL for both the drugs. The recovery studies confirmed accuracy of the proposed methods and low values of standard deviation confirmed precision of the methods. The methods were validated as per ICH guidelines.